Pengaruh Pemberian Lisin Dan Metionin Dalam Ransum Terhadap Penampilan Ayam Kampung - Pande Made Indrawan; Ni Ketut Etty Suwitari; Luh Suariani (Fakultas Pertanian, Universitas Warmadewa, 2021)
Free-range chicken is a type of local poultry that has the potential to produce eggs and meat, so it is widely cultivated by the community. The design used in this study was a completely randomized design (CRD) consisting of 4 treatments and 3 replications. The treatments were R0 = rations without lysine and methionine content (control), R1 = rations with 1% lysine content, R2 = rations with 0.5% methionine content, R3 = rations containing lysine and methionine (1% + 0.5 %). This research was conducted at Jl. Sedap Malam, Kesiman Village, Denpasar City, for 10 weeks from 14 October to 23 December 2019. Chickens used in this study were 3 week old native chickens without male and female separation with an average weight of 190-210 g / head. as many as 60 native chickens. Lysine administration and methionine administration in the ration on the appearance of native chickens aged 3-10 weeks had no significant effect (P> 0.05). The combination of lysine and methionine in the native chicken ration had a very significant effect (P <0.01) on the variables of final body weight and weight gain, while the ration consumption and ration conversion had a significant effect (P <0.05). In R3 treatment, the combination of amino acids lysine and methionine in the native chicken ration was able to show the best results on final body weight, weight gain and conversion of native chicken aged 3-10 weeks.